Harvester ants (Messor barbarus) as disturbance agents in Mediterranean grasslands (Journal of Vegetation Science, 2009)
Questions: 1. Do disturbances by harvester ants (Messor barbarus L.) affect soil properties? 2. Do they alter seed distribution? 3. Do they show a different species composition? 4 Are these changes related to seed size (length and weight)? Location: Mediterranean grasslands in central Spain, near Madrid. Methods: We recorded autumn seed banks and spring vegetation in middens, trunk trails and controls. Soil properties were also measured in middens and controls. The effect of seed weight and length was analysed after transforming data into phylogenetically independent contrasts. Results: Soil under middens is more silty and higher in potassium, organic matter and pH. Seed density and seed bank species richness increased greatly in middens, while vegetation species richness was signiﬁcantly lower in comparison to control samples. Abundance changes in this disturbance type were positively correlated with seed weight, both in seed bank and vegetation. In contrast, we only detected a slight increase in bare ground on foraging trunk trails, with no clear effects on seed bank and vegetation composition. Conclusions: Midden development is a mechanism that generates heterogeneity which favours the survival of certain large-seeded species mainly predated by ants in Mediterranean grasslands. This effect may partially neutralize the dominance of small seeded species expected from the seed predation process.